GE_GERICHTE P/18773/2017 vom 2. September 2020 - GE Cour de justice (2020)
HOMICIDE PAR NÉGLIGENCE;COAUTEUR(DROIT PÉNAL);DISPOSITIONS PÉNALES DE LA LCR | CP.117; CP.12.al3; LCR.91.al2; OCR.2.al3; OCR.96; CP.25